2020
DOI: 10.3329/bjas.v49i1.49377
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amount of red worm (Eisenia foetida) on the organic matter degradation during vermicomposting of cattle manure

Abstract: This study aimed to understand the degradation pattern of organic substances through different amount of red worms during vermicomposting of cattle manure. For this purpose, an experiment was conducted with three treatments e.g., T1 (vermicomposting of 25 kg cowdung using 50 g of red worms), T2 (vermicomposting of 25 kg cowdung using 100 g of red worms) and T3 (vermicomposting of 25 kg cowdung using 150 g of red worms) with 3 replications. Parameters studied were dry matter (DM), organic matter (OM), ash, orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…Turning operations were performed in every 10 days in T 1 helps to reduce the moisture; similarly earthworm movement in the vermicomposting pits also a cause of moisture loss in T 2 . Earthworms can consume organic substances and moves through the pit might be the cause of moisture loss during vermicomposting (Rahman et al, 2020).…”
Section: Dry Matter Changing Pattern During Composting and Vermicompostingmentioning
confidence: 99%
See 4 more Smart Citations
“…Turning operations were performed in every 10 days in T 1 helps to reduce the moisture; similarly earthworm movement in the vermicomposting pits also a cause of moisture loss in T 2 . Earthworms can consume organic substances and moves through the pit might be the cause of moisture loss during vermicomposting (Rahman et al, 2020).…”
Section: Dry Matter Changing Pattern During Composting and Vermicompostingmentioning
confidence: 99%
“…The grinding effect of its gizzard and the effect of its gut muscle movement result in the formation of casts (Garg et al, 2008). Rahman et al (2020) stated that red worm consumed the cattle manure and digested 82% of its CF within 45 days vermicomposting period. Another investigation showed that only 33% of CF was digested by microbial enzymes during 45 days of composting cattle manure with saw dust (Rana et al 2020).…”
Section: Cf Changing Pattern During Composting and Vermicompostingmentioning
confidence: 99%
See 3 more Smart Citations